Joy Hendry. 2018. Para entender la sociedad japonesa. Traducido por Francisco J. Ramos Mena. Barcelona: Bellaterra. 309 pp. - Quintairos-Soliño, Alba (Estudios de Asia y África, 2020)
Joy Hendry. 2018. Para entender la sociedad japonesa. Traducido por Francisco J. Ramos Mena. Barcelona: Bellaterra. 309 pp.